Adenosine Deaminase Levels in Cerebrospinal Fluid in Different Etiology of Meningitis (Academia Journal of Medicine, 2020)
Background: Meningitis is a medical emergency as it can be life threatening because of the inflammation proximity to brain and spinal cord.  If not recognized earlier, it can lead to serious long term neurological sequelae like deafness, epilepsy, hydrocephalus and cognitive deficits. Subjects and Methods: The study included 75 patients of meningitis, on the basis of clinical findings, CSF findings and MRI brain who were  admitted to the emergency and ICU of the hospital. Results: There were 63% male and 37% females in TBM 73.9% male and 26.1% females  in PM and 72% male and 28% females in VM group. Conclusion: CSF ADA is markedly raised in tubercular meningitis, while lower ADA  values are seen in pyogenic meningitis and viral meningitis.
Keywords: CSF-Adenosine deaminase; Differential Diagnosis of Meningitis; Tuberculous meningitis; Viral meningitis & Pyogenic meningitis